Women and youth as drivers of climate information and action in their communities - Kiogora, Joseline; Kagabo, Desire; Byandaga, Livingstone; Mvuyibwami, Patrick; Ngige, Chris; Nchanji, Eileen (2024)
ECREA Project - implemented in Kenya, Rwanda, Uganda and Tanzania - has empowered 400 farmers and extension workers as of June 2024, including 50% women and young people, co-designing and disseminating climate information services to improve the resilience of bean value chain actors against climate shocks.